A non-time division multiplexing single inductor solar and piezoelectric energy multi-input harvesting interface circuit. (April 2022) - Shi, Ge; Tong, Dike; Zeng, Wentao; Chang, Jian; Xu, Jubing; Li, Qing; Jia, Shengyao; Wang, Chenyu
Abstract: Due to time-varying and instability, single environmental energy cannot provide reliable energy for wireless sensor network nodes. Therefore, researchers propose to use multi-source synergy to provide power. Still, these circuits take time-division multiplexing or setting priority, which can only harvest one kind of environment energy at a particular moment, resulting in low energy harvesting efficiency and complex circuit structure. Also, a single vibration source is configured with multiple piezoelectric (PZT) harvesters to obtain more power. For the above questions, this paper proposes a non-time-division multiplexing single-inductor synchronous electric charge extraction circuit (NTD-SECE), which is mainly composed of rectifier bridge, peak detection circuit, control circuit, input comparison circuit, and buck-boost circuit. Theoretical analysis and experiments verify the effectiveness of the interface circuit. The results show that NTD-SECE can extract energy from photovoltaic (PV) and multi-PZTs by non-time division multiplexing, the maximum power is 450 mW. It has broad application prospects in the energy supply of low-power equipment.